Video Lectures: An Analysis of Their Useful Life Span and Sustainable Production - Santos Espino, José Miguel; Guerra Artal, Cayetano; González Betancor, Sara María (International Review of Research in Open and Distributed Learning, 2021)
The learning effectiveness of video lectures has been extensively studied by the scientific community, but research on their cost-effectiveness and sustainable production is still very scarce. To shed light on these aspects, this study has measured the useful life span and cost-effectiveness of a large catalog of video lectures produced for undergraduate courses at a Spanish university. A Kaplan–Meier survival analysis has been performed to identify factors linked to video longevity. The analysis accounted for variables such as the video production style (screencast, slideshow, chalk and talk, talking head, and on-location film) and others such as the instructional purpose and field of knowledge. The teachers involved in video production and integration have been surveyed to discover causes of video obsolescence. In addition, using life span and production cost data, the cost-effectiveness of each production style over time was estimated. The results suggest that production style affects video longevity, and in particular, dynamic visuals are more related to longer life spans compared with static contents. Screencast stands out as the most cost-effective production style, having the best ratio of life span to production effort. Some practical suggestions are provided for producing video lectures with higher longevity expectations.